2019
DOI: 10.1186/s12931-019-1002-5
|View full text |Cite
|
Sign up to set email alerts
|

Persistent exercise limitation after successful pulmonary endoarterectomy: frequency and determinants

Abstract: Background After successful pulmonary endoarterectomy (PEA), patients may still suffer from exercise limitation, despite normal pulmonary vascular resistance. We sought to assess the proportion of these patients after the extension of PEA to frail patients, and the determinants of exercise limitation. Methods Out of 553 patients treated with PEA from 2008 to 2016 at our institution, a cohort of 261 patients was followed up at 12 months. They underwent clinical, haemodyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Chronic thromboembolic pulmonary hypertension patients treated with PEA had a worsened lung diffusion capacity, while patients with CTEPH treated with BPA had an improved lung ventilation. Previous studies have revealed that the lung diffusion capacity in CTEPH patients decreased in the short term (3 weeks) after PEA ( 14 ), and could persist for more than 1 year ( 31 ), which were consistent with our study ( Table 2 ). Compared with the deterioration of the lung diffusion capacity in CTEPH patients treated with PEA, the impaired lung diffusion capacity was not changed ( P = 0.679, Supplementary Table 1 ) in CTEPH patients treated with BPA in both our study and previous studies ( 26 , 32 ).…”
Section: Discussionsupporting
confidence: 93%
“…Chronic thromboembolic pulmonary hypertension patients treated with PEA had a worsened lung diffusion capacity, while patients with CTEPH treated with BPA had an improved lung ventilation. Previous studies have revealed that the lung diffusion capacity in CTEPH patients decreased in the short term (3 weeks) after PEA ( 14 ), and could persist for more than 1 year ( 31 ), which were consistent with our study ( Table 2 ). Compared with the deterioration of the lung diffusion capacity in CTEPH patients treated with PEA, the impaired lung diffusion capacity was not changed ( P = 0.679, Supplementary Table 1 ) in CTEPH patients treated with BPA in both our study and previous studies ( 26 , 32 ).…”
Section: Discussionsupporting
confidence: 93%
“…More consistent correlations were reported between exercise parameters and pulmonary arterial compliance [26,27]. In a recent study, 41% of patients were reported to have persistent exercise limitation 12 months after PEA, as defined by a distance walked <400 m in a modified Bruce protocol [28]. However, the cut-off of 400 m was somewhat arbitrary, and based on the median distance walked in their previous analysis [29].…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, autonomic balance [24, 25] and endothelial [26] and skeletal muscle function [27] can be improved by increasing oxygen delivery and by reversing both systemic and local inflammatory processes. Therefore, exercise training may be a useful add-on therapy to PEA to also further improve those exercise-limiting factors which persist even after the normalisation of haemodynamics, as described by Corsico et al [10] in up to 40% of patients. Specialised rehabilitation programs have also shown to significantly improved exercise capacity in other conditions post-surgery, such as after heart transplantation [28].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of 251 CTEPH patients with follow-up until 12 months after PEA showed a persistent exercise limitation in almost 40% of patients despite normalisation of PVR and haemodynamics [10]. This limitation was characterised by a multifactorial aetiology also involving respiratory function abnormalities.…”
Section: Introductionmentioning
confidence: 99%